Submerged aesthetics, emerging policies: the role of eco-art in marine conservation through The House of Fish project (Itinera, 2025)
This article explores how eco-art can meaningfully contribute to marine conservation by integrating aesthetic expression with ecological restoration and community engagement. Focusing on The House of Fish—an underwater sculpture park off the coast of Tuscany initiated by fisherman Paolo Fanciulli—the study examines how Carrara marble sculptures function as artificial reefs, deterrents to illegal trawling, and catalysts for sustainable tourism through practices such as pescaturismo. The project is situated within Italy’s broader tradition of environmentally engaged art, drawing on influences from Arte Povera and relational aesthetics to consider how artistic interventions can support ecological regeneration. In doing so, the paper highlights eco-art’s capacity to shift environmental narratives from abstract policy to tangible, place-based experience. It also assesses how such initiatives align with national and international policy frameworks, including Italy’s National Biodiversity Strategy, the EU Marine Strategy Framework Directive, and the Sustainable Development Goals. Ultimately, the article argues that eco-art is more than symbolic—it offers a compelling model for integrating cultural practice into environmental governance. To promote eco-art as a policy-supported practice, the article proposes a set of recommendations for adoption at both national and international levels.
Keywords: Eco-Art; Marine Conservation; Environmental Policy; Pescaturismo; The House of Fish